Energy Efficiency Analysis of LED, CFL, and Incandescent Bulbs with Smart Energy Management (SEM) Technology - Supriyono, Lawrence Adi; Fitrianto, Yuli; Setiawan, Dwi; Putranto, Kartiko Eko; Aldila, Amalia Shifa (LPPM UNIKA Santo Thomas Medan, 2024)
This study focuses on the comparative energy efficiency analysis of LED, CFL, and incandescent bulbs to assess the potential savings offered by LED technology. With growing global concerns about energy consumption and carbon reduction, it is essential to eval_uate lighting options based on energy efficiency. Incandescent bulbs, though widely used, are inefficient as they emit more energy as heat than light. Compact Fluorescent Lamps (CFLs) are more energy-efficient but have a shorter lifespan compared to LEDs, making them less environmentally friendly. In this research, the real-time power consumption of each bulb type is measured using ACS712 and ZMPT101B sensors, connected to an Arduino Uno R3 microcontroller. The ACS712 sensor is used to monitor electrical current, while the ZMPT101B sensor detects voltage, enabling accurate energy consumption calculations. All bulbs are tested under identical conditions, providing clear, comparative data on their energy efficiencies. The analysis demonstrates that LED bulbs not only offer lower energy consumption but also result in long-term environmental and economic benefits. These findings suggest significant savings in electricity costs, supporting the shift towards energy-efficient LED lighting.